1998
DOI: 10.1029/98jb01273
|View full text |Cite
|
Sign up to set email alerts
|

Synergy of active and passive airborne thermal infrared systems for surface compositional mapping

Abstract: Abstract. NASA thermal infrared multispectral scanner (TIMS) and Commonwealth Scientific Industrial Research Organisation mid-infrared airborne CO2 laser spectrometer (MIRACO2LAS) data were acquired over the Mount Fitton area, South Australia, in order to evaluate their combined use for geological mapping and mineral exploration. TIMS is a passive, imaging system with six spectral bands in the thermal infrared wavelength region (8-12/xm), whereas MIRACO2LAS is an active, profiling system with -100 spectral ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…The TIR (8-14 m) and the MIR (3-5 m) are areas that have great potential for geologic remote sensing studies, but that have been under-investigated probably due to (1) the complexity of the physics (e.g., volume scattering effects in the TIR and emissivity and temperature interference in the MIR) and (2) lack of field/laboratory spectrometers and (airborne/spaceborne) hyperspectral data. In the early 1990s, Mike Abrams showed the added value of combined TIR and SWIR observations (Abrams et al, 1991;Hook et al, 1998). From TIR multispectral scanner data Simon Hook and co-authors showed the type of information that could be revealed (Hook et al, 1992(Hook et al, , 1994Hook and Kahle, 1996).…”
Section: Applications In Geology: the Tir Rangementioning
confidence: 95%
“…The TIR (8-14 m) and the MIR (3-5 m) are areas that have great potential for geologic remote sensing studies, but that have been under-investigated probably due to (1) the complexity of the physics (e.g., volume scattering effects in the TIR and emissivity and temperature interference in the MIR) and (2) lack of field/laboratory spectrometers and (airborne/spaceborne) hyperspectral data. In the early 1990s, Mike Abrams showed the added value of combined TIR and SWIR observations (Abrams et al, 1991;Hook et al, 1998). From TIR multispectral scanner data Simon Hook and co-authors showed the type of information that could be revealed (Hook et al, 1992(Hook et al, , 1994Hook and Kahle, 1996).…”
Section: Applications In Geology: the Tir Rangementioning
confidence: 95%
“…These features are related to the differences in the SiO content in the soil, which has minimal emissivity and therefore maximum absorption (reststrahlen effect). This behavior is observed in silicates, such as quartz, having reststrahlen effects observed around 8,2µm and 9,3µm (Hook et al 1998). Consequently, TIR region (8µm-14µm) is effective for this kind of study, in which the material emissive properties are predominant relative to its reflective properties (Hook et al 2005;Li et al 2013;Grondona et al 2019).…”
Section: Pseudo-invariant Targetmentioning
confidence: 96%
“…Figura 4 -Fluxograma de etapas de processamento das imagens ASTER/TIR. Hook et al, 1998;Ramsey et al, 1999). O alto grau de correlac ¸ão entre bandas em dados termais deve-se ao fato de que os valores de radiância são func ¸ão direta da temperatura e emissividade da superfície (Vaughan et al, 2005).…”
Section: Composic ¸õEs Coloridas E Realce Por Decorrelac ¸ãOunclassified